Single-Source Precursors for Chemical Solution Deposition of Up-Converting NaLnF4 Thin Films - Artem Shevchenko; Andrei Anosov; Daria Blinnikova; Dimitry Grebenyuk; Dmitry Tsymbarenko (Metals, 2022)
Novel single-source precursors based on sodium and lanthanide pentafluoropropionates have been developed for chemical solution deposition of NaLnF4 thin films (Ln = Y, Yb, Er, Tm). A series of [Ln2(pfp)6Qn] (Q = H2O, diglyme) and mixed-metal NaLn(pfp)4Qn were synthesized and characterized by X-ray diffraction (XRD) and thermogravimetric analysis (TG-DTA). Thermal decomposition of individual Na(pfp) and Ln(pfp)3 occurs at different temperatures while single-source NaLn(pfp)4 decomposes with the transformation to NaLnF4 in a single stage at 280 °C. Further crystallization of NaLnF4 was studied by variable-temperature powder XRD, which shows two phase transformations from cubic NaLnF4 to hexagonal NaLnF4 at 310 °C and back to a high-temperature cubic phase at 560 °C. The thin films of NaY0.78Yb0.2Er0.02F4 prepared by the dip-coating technique on Al2O3 substrates showed intense up-converting luminescence in green and blue regions under 980 nm excitation.